Implicit approximate decoupling procedure with Crank–Nicolson scheme for bandpass symmetric rotationally geophysical problems. Issue 2 (6th November 2021) - Wu, Shihong; Dong, Yunyun; Liu, Lining; Su, Feng; Chen, Xiangguang
Abstract: To efficient simulate symmetric rotationally geophysical problems, implicit Crank–Nicolson (CN) scheme incorporated with approximate decoupling procedure is proposed in the body of revolution (BOR) finite‐difference time‐domain (FDTD) algorithm. For further absorption of large number of low‐frequency waves in bandpass simulation, complex envelope method is incorporated with the perfectly matched layer implementation. To be more specific, the proposed implementation shows advantages in terms of improved efficiency, considerable accuracy, and remarkable absorption. To demonstrate effectiveness and efficiency of the proposed implementation, geophysical numerical examples are carried out in the BOR‐FDTD domain. Through different numerical examples, it can be concluded from simulation results that the proposed implementation can obtain admirable entire performance in bandpass geophysical simulation. In addition, it can also be illustrated that it can keep stable when time step surpasses far beyond the Courant–Friedrichs‐ Levy condition.